Yeasts killer/sensitivity phenotypes and halotolerance - Aguiar, Cristina (2000)
Yeast killer phenotype is not uniformly distributed within certain genera or even within some species. Salt has been described as enhancing killer action, especially in strains that have been isolated from salt environments. The aim of this work was to evaluate the extent of the correlation, if any, between killer/sensitivity and salt-stress tolerance phenotypes. A set of 58 different yeast strains (46 species) was studied. As it has been previously described, tolerance to salt stress can be classified in four major classes of tolerance: 1, 2, 3 and 4 M NaCl. Investigation of killer and sensitivity phenotypes was carried out in the absence and in the presence of NaCl from 0 to 3.5 M, in 0.5 M increments. On the basis of this study, two different groups of yeasts were established. One group was mainly composed of the more halotolerant killer yeasts, which also displayed an increase of killer spectrum in the presence of salt in the assay. The other group included the less halotolerant strains, whose killer spectrum was less significant and either did not vary consistently with salt stress in the assay or decreased in its presence. Although killer activity was found in yeasts belonging to the various classes of salt-stress tolerance, the percentage of strains showing this capacity increased significantly for the classes of higher halotolerance, while the percentage fraction of sensitive strains remained approximately constant. This suggests a phenotypic relationship between high halotolerance and killer capacity manifestation in the presence of high salt concentrations, which is not a consequence of an increase in sensitivity to salt stress of the target strains.